Solar-Powered Smart Irrigation for Chilli Plants - Md Armaludin, Inshyrah Harlina Alyea Laila; Abdullah, Mohammad Faiz Liew (Evolution in Electrical and Electronic Engineering, 2026)
The project aims to develop a Solar-power Smart Irrigation System for chilli plants, which are sensitive to water management. This smart water irrigation system should reduce water waste and manual intervention, and encourage the use of renewable energy. It is equipped with multiple sensors, including a soil moisture sensor, a pH sensor, and a close-range ultrasonic water sensor, which are managed by an ESP32 microcontroller to detect real-time soil and environmental conditions. Using the system, water can be optimised for chilli plant growth because it automatically irrigates in accordance with set soil moisture levels. It is solar-powered, using a solar photovoltaic panel and a battery-charging module, making it independent of the grid. It has also used an Internet of Things (IoT) platform, the Blynk application, for real-time tracking and triggering alerts to users via a mobile interface. Empirical observations indicate that this system can ensure the best level of soil moisture, energy efficiency, and non-pollution, and is usable across different sun exposure regimes. It can be helpful for small-scale farming, urban farming, and at-home gardens, and it focuses on the potential of solar energy and smart irrigation for sustainable chilli cultivation.